(untitled) (LACCEI, 2024)
This research established the relationship between human resources and innovation, focusing on three dimensions of human resources: planning, integration and development, and two dimensions of innovation: talent and digital technology for Mype entrepreneurs from Huaura, Huaral and ravine. A quantitative approach was used through the administration of surveys to a sample of 425 Mype companies. The results indicate that planning and development of human resources are significantly related to innovation, while integration is not. In addition, it was found that both talent and digital technology have a positive and significant relationship with innovation. The study was based on the field work carried out and the findings have implications for the management of human resources and innovation in companies confirmed by high reliability values with the Cronbach Alpha method of 69.6% for human resources, such as This is confirmed by [1] Spearman’s correlation of 0.426 and 0.455 in the correlation when doing multiple regression, which indicates moderate correlation, suggest that attention should be paid to the planning and development of human resources and the adoption of digital technologies to promote innovation in organizations